A case study for biochemical application porting in european grids and clouds. (15th August 2013) - Kertesz, Attila; Otvos, Ferenc; Kacsuk, Peter; Merelli, Ivan; Pérez‐Sánchez, Horacio; Gesing, Sandra
SUMMARY Researchers of various disciplines ranging from Life Sciences and Astronomy to Computational Chemistry create and use scientific applications producing large amount of complex data relying heavily on compute‐intensive modeling, simulation, and analysis. Grid computing provides an efficient way for parallelizing and gridifying computational and data intensive applications of various research fields including molecular dynamics. In this paper, we examine a biochemical application that generates conformers by unconstrained molecular dynamics at high temperature to overcome conformational bias then finishes each conformer by simulated annealing and energy minimization to obtain reliable structures. We provide a general way for turning biochemical applications into scientific workflows that can be executed through Web‐based portals exploiting the computational power of available distributed computing infrastructures such as production grids, clusters, supercomputers, or clouds. First, we describe the application porting process, then provide experimental results that show the achieved speed‐up of the ported application on three different infrastructure; finally, we show how to design a more attractive and easily usable graphical interface for this application. Copyright © 2013 John Wiley & Sons, Ltd.